A Burnt Child : A Novel - Dagerman, Stig, 1923-1954 (Book collections on Project MUSE., 2013)
Set in a working-class neighborhood in Stockholm, A Burnt Child revolves around a young man named Bengt who falls into deep, private turmoil with the unexpected death of his mother. Written in a taut and beautifully naturalistic tone, it remains Stig Dagerman's most widely read novel and is one of the crowning works of his short but celebrated career.